DINAMIKA PENDIDIKAN AGAMA KRISTEN TINJAUAN HISTORIS, KONTEKSTUAL, DAN PROSPEKTIF - Arimiu Arimiu; Septhemi Septhemi; Novita Sarira; Nelti Nelpika Minanga; Hotniel Aldi Winata Bombing (CV. Adiba Aisha Amira, 2025)
This article examines the dynamics of Christian Religious Education (PAK) in Indonesia through historical, contextual, and prospective approaches. From the colonial period to the independence era, PAK has undergone significant developments in terms of curriculum, methods, and theological orientation. In the current context, PAK faces complex challenges such as globalization, secularism, religious plurality, and the development of digital technology. To respond to these challenges, contextualization and innovation strategies are crucial to ensure PAK remains relevant, transformative, and capable of shaping strong Christian character. This article also proposes a direction for future PAK development that emphasizes strengthening teacher competency, integrating faith and life, and synergy between the church, schools, and society. Through this study, it is hoped that PAK can continue to be a moral and spiritual force that plays a role in shaping a generation of faithful, critical, and integrated Christians in Indonesia's pluralistic and dynamic society.